Social capital and individual income level in Peninsular Malaysia / Mohd Nasir Mohd Saukani - Mohd Nasir , Mohd Saukani (2018)
For decades-long, economists have been relying on the existing conventional capital (i.e. physical capital, financial capital, and human capital) in finding an exact explanation on factors that contributes to income inequality. The new wave of economic thinking has proposed that the scope of analysis should be broaden by taking into account social capital i.e. the relational aspect (capabilities to interact and build relation/networks) of human as another potential determinant of inequality. Theorists and advocates of this relational capital firmly believe that social capital acts as a lubricant to smooth the economic activity and complement the existing conventional capital as an engine of economic growth, enhances individual income/wellbeing and alleviate income inequality. The potential influence of this new economic capital has been supported by an increasing volume of empirical studies that has come out with a promising significant result. Nevertheless two main issues need to be tackled before the potential of social capital can be recognized and accepted especially by the main stream economist. First on the issue of definition and second on the measurement of social capital. In a developing country such as Malaysia, income inequality remains an unresolved issue despite lot of efforts has been taken by government to tackle it. The aim of this study is three-fold: first, to propose a new precise definition of social capital and to determine components of social capital from the Malaysian perspective: second, to construct the composite score of social capital in Malaysia perspective; and finally to analyze the impact of social capital on individual income using the composites scores of social capital as a proxy. The outcome of this study is crucial in giving a wider perspective on factors that determine the prolonged issues of disparity in income facing by Malaysian. Using data of 2,443 individual (head of household and working household member), collected from field study in selected states and Federal Territory (i.e. Kedah, Selangor, F.T. Kuala Lumpur, Johor and Terengganu) between 2012 and 2013, this study applied the multilevel modeling (MLM) analysis technique in analyzing the impact of social capital on individual income. MLM technique enable the influence of social capital on individual income to be analyzed accordingly to the individual-level (i.e. head of household and working household member) and the group-level (district) in this study. Result indicates that influence of spirituality and culture is the new component of social capital in the Malaysian perspective. MLM analysis too indicates the significant influence of social capital on individual income at individual and within-group level. In line with empirical studies, the influence of social capital on income was found to be lower compared to human capital and other control variable. This study too indicates that social capital variable was actually a moderator and not a mediators in influencing individual income in Malaysia.